Alternative approach techniques to support home islamic boarding schools using virtual learning technology - Rohman, Abdul; Muda, Lisdawati; Posangi, Said Subhan; Yahiji, Kasim; Munirah, Munirah (Linguistics and Culture Review, 2021)
Digital technology-based learning or virtual learning is a method of learning in schools and an alternative learning method for Islamic boarding schools, including Islamic education boarding schools from house to house. Previous findings have proven the effectiveness of using a virtual learning approach for university and boarding schools. However, few people know that this virtual approach can also be used for alternative home-to-house learning for the younger generation who want to study religion. For this reason, we have carried out data collection and in-depth analysis involving a coding system and high data interpretation under a phenomenological approach that we have resulted out with very valid and reliable findings. The data we use comes from a database of technology and learning journal publications, books, and educational technology development websites, all of which have become the primary data for this study. It is hoped that this finding is a valuable input in efforts to solve the problem of learning Islamic religion from house to house apart from pesantren and Islamic schools.